Toughening effects of well-dispersed carboxylated styrene-butadiene latex powders on the properties of oil well cement. (18th July 2022) - Zhao, Jiaqi; Hu, Miaomiao; Liu, Wenming; Feng, Jianghui; Zhang, Hang; Liu, Ming; Guo, Jintang
Graphical abstract: Highlights: The well-dispersed latex powders SISBR was prepared by incorporating itaconic acid. The strong electrostatic repulsive forces were responsible for its good dispersion. The toughening effect of SISBR powders is better than that of liquid SISBR latex. Abstract: Latex has been extensively used in oil well cementing. Since the poor stability of liquid latex exposed during their transportation and storage, the well-dispersed latex powder is in urgent need. Herein, the well-dispersed sulfonic acid group modified latex powder SISBR was synthesized by incorporating itaconic acid (IA) into SSBR latex. Results manifested that introducing IA enhanced the stability of latex powders dispersed in water, and the modified latex powders can disperse completely in water by simply manual stirring. Then, effects of SISBR powders on cement properties were tested. Results indicated that the –COOH from IA is beneficial to the dispersion of cement paste, but over-addition resulted in serious retarding of hydration, thereby the optimal content was determined as 2.4%. At this dosage, 7-day flexural strength of cement was improved by 49.5%, which was even better than that of the corresponding liquid SISBR latex with the same solid content.